Fatty Acid Composition, Tocopherol and Sterol Contents in Linseed (Linum usitatissimum L.) Varieties - Bertrand Matthäus; Mehmet Musa Özcan (Iranian Journal of Chemistry & Chemical Engineering, 2017)
The oil contents of linseeds were determined between 39.9% (Antares) and 43.3%  (Railinus). The oleic acid contents of seed oils varied between 0.8% (Maroc) and 24.8 (Railinus). The linoleic acid contents of linseed oil change between 10.2% (Avangard) and 48.2% (Maroc), while the palmitic acid of oils ranged from 4.8% (Antares) to 6.1% (Maroc), stearic acid contents ranged between 4.7% (Avangard) to 23.5% (Maroc). Also, linolenic acid contents of Avangard oil was higher (59.9%) than those of results of other linseed oils. The P8 contents of linseed oil change between 1.1 mg/kg (Railinus) and 16.4 mg/kg (Avangard). Also, the δ-tocopherol content of Railinus oil was also higher (262.7 mg/kg) than those of other linseed oils (0.3-0.4 mg/kg).The total tocopherol in Railinus seed oil was higher (437.4 mg/100 g) (p<0.05) than that of Maroc seed oil (30.3 mg/100 g).